Extracellular matrix component expression in human pluripotent stem cell-derived retinal organoids recapitulates retinogenesis in vivo and reveals an important role for IMPG1 and CD44 in the development of photoreceptors and interphotoreceptor matrix. (1st July 2018) - Felemban, Majed; Dorgau, Birthe; Hunt, Nicola Claire; Hallam, Dean; Zerti, Darin; Bauer, Roman; Ding, Yuchun; Collin, Joseph; Steel, David; Krasnogor, Natalio; Al-Aama, Jumana; Lindsay, Susan; et al.
Graphical abstract: Abstract: The extracellular matrix (ECM) plays an important role in numerous processes including cellular proliferation, differentiation, migration, maturation, adhesion guidance and axonal growth. To date, there has been no detailed analysis of the ECM distribution during retinal ontogenesis in humans and the functional importance of many ECM components is poorly understood. In this study, the expression of key ECM components in adult mouse and monkey retina, developing and adult human retina and retinal organoids derived from human pluripotent stem cells was studied. Our data indicate that basement membrane ECMs (Fibronectin and Collagen IV) were expressed in Bruch's membrane and the inner limiting membrane of the developing human retina, whilst the hyalectins (Versican and Brevican), cluster of differentiation 44 (CD44), photoreceptor-specific ECMs Interphotoreceptor Matrix Proteoglycan 1 (IMPG1) and Interphotoreceptor Matrix Proteoglycan 2 (IMPG2) were detected in the developing interphotoreceptor matrix (IPM). The expression of IMPG1, Versican and Brevican in the developing IPM was conserved between human developing retina and human pluripotent stem cell-derived retinal organoids. Blocking the action of CD44 and IMPG1 in pluripotent stem cell derived retinal organoids affected the development of photoreceptors, their inner/outer segments and connecting cilia and disrupted IPM formation, with IMPG1 having an earlier and more significant impact. Together, our data suggest an important role for IMPG1 and CD44 in the development of photoreceptors and IPM formation during human retinogenesis. Statement of Significance: The expression and the role of many extracellular matrix (ECM) components during human retinal development is not fully understood. In this study, expression of key ECM components (Collagen IV, Fibronectin, Brevican, Versican, IMPG1 and IMPG2) was investigated during human retinal ontogenesis. Collagen IV and Fibronectin were expressed in Bruch's membrane; whereas Brevican, Versican, IMPG1 & IMPG2 in the developing interphotoreceptor matrix (IPM). Retinal organoids were successfully generated from pluripotent stem cells. The expression of ECM components was examined in the retinal organoids and found to recapitulate human retinal development in vivo . Using functional blocking experiments, we were able to highlight an important role for IMPG1 and CD44 in the development of photoreceptors and IPM formation.